Human Capital Upgrading, Social Inclusion and New Suez Canal Economic Zone - Biltagy, Marwa; Nassar, Heba (Economy of Regions, 2020)
Creating society for all individuals by social inclusion is the best way to fight poverty and social exclusion. The construction of socially inclusive communities should be supported and encouraged by all partners in society not only the government. Thus, societies should create partnerships among all actors. These partnerships should promote complementary strategies for change, addressing the broad range of economic, social and environmental policies. It is time for economic zones to play their part in achieving social inclusion and sustainable development. Special Economic Zones are known for supporting the strategy of economic reform, decreasing the unemployment ratio and attracting new investments. The paper aims to propose design elements for creating socially inclusive Suez Canal Economic Zone. For this purpose, we introduced essential strategies of building an inclusive society. Moreover, we analysed inclusive growth indicators and the main characteristics of firms and workers in the Suez Canal Zone. The results include attracting foreign direct investment and increasing exports, achieving sustainable and inclusive green strategies that encompassing exports and investment creation, enabling capacity building, generating employment opportunities, assuring trickling down effect and creating linkages with the local economy to improve socio-economic conditions and eliminating regional disparities.